Unify Religious and Ethnic Identity: Can it be New Approaches for Community Development in Contemporary Muslim China? - Fatima Yang-Guiping (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2021)
Nowadays, religion has continuously been a supposition that separated from the role of development. However, the harmonious co-existence between Islam and Confucianism has been a new trend for sustainable development. Through harmonious dialogue among ethnicity and cultural society, community development issues encouraged all stakeholders to build a balanced life. This study aims to deliberate interpretation of the historical experience of co-existence between Islam and Confucianism amidst common heritage as a new instrument of national development in China. This study uses a historical approach and qualitative methods, in which the article answered scepticism that religions only could produce hatred, conflict, apartheid, and inclusivism. The result shows that made Islam an indispensable part of Chinese civilization. There could contribute to the contemporary global dialogue that is resolving the conflict among religions and nationalists. Instead, there makes strengthen for sustainable community development affected economic stability. The paper concludes that escalating the harmonious co-existence and religious dialogue should be rising in the public sphere as a new trend for sustain and prosperous people with minority groups in contemporary China.